Exploring Sustainable Silicone Crosslinking Motifs - Li, Angela (My University, 2024)
Silicone materials are widely used – they are in the bathroom, they come in the mail, and they are in everyone’s pockets. However, traditional silicone crosslinking methods normally involve the use of toxic or endangered metal catalysts that remain trapped within the material. While these crosslinking methods are convenient and easy to perform, there remains a desire to explore alternative, more sustainable curing methods. This research project explored the use of both covalent bonds between natural materials using oxidative phenolic coupling and dynamic boronic esters as alternative crosslinking strategies. Phenolic coupling is a reaction that occurs through phenoxy radicals and is widely employed by nature. We exploited this strategy by attaching a naturally occurring phenolic compound, eugenol, onto silicone copolymers and then curing the materials oxidatively. By mimicking this natural process, elastomeric materials that possess antioxidant abilities of varying hardnesses could be made. Another curing process exploited dynamic boronic ester formation between a glucose residue and boronic acid. This equilibrium process between two different silicone polymers modified with the two constituents created viscoelastic materials with a range of rheological properties which were further modified by dative bonds between boron and nitrogen. In either case, routes to silicone materials that bypass the need for metal catalysts were achieved.